Assessment of Personality in Basque Public Sector Employees and Its Role in Predicting Organizational Citizenship Behaviors in Selection Processes - Balluerka, Nekane; Gorostiaga, Arantxa; Rodríguez-López, Alexander; Aliri, Jone (Frontiers in Psychology, 2021)
Organizational citizenship behaviors (OCBs) are an important aspect of job performance as they enhance the effectiveness of organizations. Research has shown that personality is a moderate predictor of job performance. This study, involving a sample of 678 public sector employees in the Basque Country (northern Spain), pursued two aims: first, to develop and validate a Basque-language version of the Overall Personality Assessment Scale (OPERAS) (Vigil-Colet et al., 2013), a scale designed to assess the Big Five personality factors in a wide range of settings; and second, to examine whether person-organization fit (PO fit) and adaptive performance improve the capacity of personality to predict OCBs. The results indicated that the adapted scale was a suitable instrument for assessing personality in the Basque-speaking population. Furthermore, PO fit and adaptive performance improved the capacity of personality to predict OCBs. Based on these results, we propose a new predictive model that may enhance the efficiency of personnel selection processes.